2020
DOI: 10.2147/ott.s283751
|View full text |Cite
|
Sign up to set email alerts
|

GRHL2 Acts as an Anti-Oncogene in Bladder Cancer by Regulating ZEB1 in Epithelial-Mesenchymal Transition (EMT) Process [Erratum]

Abstract: OncoTargets and Therapy is an international, peer-reviewed, open access journal focusing on the pathological basis of all cancers, potential targets for therapy and treatment protocols employed to improve the management of cancer patients. The journal also focuses on the impact of management programs and new therapeutic agents and protocols on patient perspectives such as quality of life, adherence and satisfaction. The manuscript management system is completely online and includes a very quick and fair peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…2e, f), and significantly enriched for transcription factors (16.45%, Fisher’s Exact Test odds ratio = 3.12, p value = 5.192e-07) defined by Lambert et al 70 , consisting of several FOX family and Zinc finger family members (Supplementary Table 4). Those also include GRHL2 , which was previously identified as anti-oncogene in bladder carcinoma by regulating the expression of ZEB1 gene thus preventing EMT both in cell lines and tissue samples 71 . In addition, KDM5B, which is a H3K4 demethylase 72 and regulated by NMIBC specific enhancers, is also implicated in progression of bladder carcinoma 73 .…”
Section: Resultsmentioning
confidence: 99%
“…2e, f), and significantly enriched for transcription factors (16.45%, Fisher’s Exact Test odds ratio = 3.12, p value = 5.192e-07) defined by Lambert et al 70 , consisting of several FOX family and Zinc finger family members (Supplementary Table 4). Those also include GRHL2 , which was previously identified as anti-oncogene in bladder carcinoma by regulating the expression of ZEB1 gene thus preventing EMT both in cell lines and tissue samples 71 . In addition, KDM5B, which is a H3K4 demethylase 72 and regulated by NMIBC specific enhancers, is also implicated in progression of bladder carcinoma 73 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that Grhl2 is involved in the EMT process of tumor cells by binding to ZEB1 promoter to inhibit its transcription. 32 However, this study also found that ZEB1 was not involved in Grhl2-/RBM25-regulated cell migration and EMT. Next, we will further investigate how Grhl2 regulates the EMT of trophoblasts during PE.…”
Section: Discussionmentioning
confidence: 51%
“…Grhl2 inhibits bladder cancer cell proliferation and inhibits EMT process by downregulating ZEB1 expression. 32 Our group previous study revealed that Grhl2 was highly expressed in PE placenta, and circTNRC18-induced miR-762 inhibited upregulation of Grhl2, leading to trophoblast migration and EMT. 16 In this study, we found that Grhl2 was involved in RBM25-regulated trophoblast cells migration, invasion, and EMT.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This regulation controls the anterior migration of gastrulation in embryogenesis [215] and contributes to the tumor invasion, stem-like motility and chemoresistance [216]. In addition, not only SNAIL1, the related EMT transcription factors such as ZEB1 and twist1 were also found to be regulated by MET-related dominant molecules, the OVOL1/2 [217][218][219], and GRHL2 [220,221], and such factors were involved in wound healing and embryogenesis as well [222][223][224]. According to the report by Pienta et al, both OVOL1/2 serve as negative regulators in prostate or breast cancer, in which overexpression of OVOL1 or OVOL2 can decrease ZEB1 to restrict cells EMT, consequently suppressing metastasis [225].…”
Section: Upstream Regulators Contribute To Determining the Emt/met In Cancersmentioning
confidence: 99%